Kajian Pancasila Sebagai Pilar Filosofis Demokrasi Indonesia dalam Pembentukan Kebijakan Hukum yang Berkeadilan - Cindy Nurhasannah; Meri Fernandes Sinaga; Dinda Amalia Nasution; Herlinda Herlinda; Brent Hizkia Pandang; Ramsul Nababan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the role of Pancasila as a philosophical pillar in strengthening Indonesian democracy and shaping just legal policies amidst the dynamics of legal changes. The research background highlights the challenges in actualizing Pancasila's values within the legal system, reflected in the incongruence of legal policies with the principle of justice, limited public participation, and obstacles in the era of globalization. This qualitative study, employing a literature review method, aims to analyze the application of Pancasila's values in addressing legal challenges and to identify the constraints in its implementation as a foundation for democracy. The findings indicate a mismatch between legal policies and Pancasila's values due to political factors, a lack of understanding, complex bureaucracy, and systemic injustice. Limited public participation in policy formulation also poses a constraint. The implications of this research underscore the need to enhance the understanding and internalization of Pancasila's values in the legal policy-making process, as well as to increase public participation to achieve a more just and democratic legal system in accordance with the ideals of Pancasila.